(untitled) (Bangladesh Journal of Nuclear Medicine, 2023)
Familial hypocalciuric hypercalcemia (FHH) is a rare, lifelong, benign condition with an autosomal dominant pattern of inheritance. FHH is clinically distinguished by mild to moderate PTH-dependent hypercalcemia and normal to significantly reduced urinary calcium excretion despite elevated serum calcium. FHH is usually caused by a heterozygous loss-of-function mutation in the calcium-sensing receptor gene (CASR). It should be differentiated from primary hyperparathyroidism (PHPT). The reported case of a 10-year-old girl presented with symptomatic hypercalcemia, elevated intact parathyroid hormone, and a vitamin D deficiency. 99mTc-Sestamibi scan failed to detect any abnormalities, but high-resolution ultrasound (HRUS) of the neck revealed a right inferior parathyroid adenoma, which was excised with a focused parathyroidectomy. Although the patient’s calcium and iPTH levels normalized initially, they started rising within a few days. Bangladesh J. Nuclear Med. 26(1): 62-65, 2023